PENGARUH ETIKA PROFESI, KOMPETENSI KONSULTAN PAJAK, MACHIAVELLIANISME TERHADAP PENGAMBILAN KEPUTUSAN ETIS KONSULTAN PAJAK DIMODERASI LOCUS OF CONTROL: (Studi Kasus Pada Anggota Ikatan Konsultan Pajak Indonesia Wilayah Banten) - Ratri Widiyanti; Suhendra (LPPM Universitas Buddhi Dharma, 2025)
Ethical decision-making by tax consultants in Indonesia faces significant challenges due to rising cases of unethical practices, such as bribery and fraudulent tax reporting. These issues undermine public trust and compliance with tax regulations, highlighting the urgent need to examine factors influencing ethical judgments in this profession. This study investigates how Professional Ethics, Tax Consultant Competency, and Machiavellianism affect Ethical Decision-Making, with Locus of Control as a moderating variable. This study aims to provide empirical evidence to strengthen ethical standards in Indonesia’s tax consulting sector. A quantitative associative approach was employed, using data from 301 certified tax consultants registered with the Indonesian Tax Consultants Association in Banten, and data were collected via questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS software. The study show that Professional Ethics significantly affects Ethical Decision-Making, Tax Consultant Competence significantly affects Ethical Decision-Making, Machiavellianism significantly affects Ethical Decision-Making. Locus of Control moderates the relationship between Professional Ethics and Ethical Decision-Making, Locus of Control does not moderate Tax Consultant Competence on Ethical Decision-Making, and Locus of Control does not moderate the Machiavellianism on Ethical Decision-Making. Strengthening professional ethics and competency through training, coupled with measures to mitigate Machiavellian traits (e.g., integrity cultures and supervision), is critical for improving ethical decision-making. Future research should explore alternative moderators beyond locus of control.